Manajemen Sarana dan Prasarana dalam Upaya Meningkatkan Mutu Layanan Pendidikan di Sma Negeri 1 Purwakarta - R. Supyan Sauri; Ayi Najmul Hidayat; Raden Dewangga Tresna Erawan; Lufi Ardiana; Desemberi Trianugrahwati (Journal on Education, 2023)
Management of infrastrucuture and Facilities is one of many fields of quality that need to be improved. Infrastructure is one of the supporting factors in the learning process. In the concept of The Juran Trilogy or commonly called the Juran Trilogy can be applied in schools as an effort to improve the quality of educational services. The objectives of this research are: (1) to describe the planning of infrastructure facilities at SMA Negeri 1 Purwakarta, (2) to describe the control of infrastructure at SMA Negeri 1 Purwakarta, (3) to describe the improvement of infrastructure facilities at SMA Negeri 1 Purwakarta. This study used a qualitative approach with case study method. While the data collection techniques used include: (1) in-depth interviews, (2) participant observation, and (3) documentation study. Data analysis techniques using data reduction, data presentation, data verification. While the data validity technique uses credibility, triangulation, transferability, dependability and confirmability. The results showed that: (1) the planning of infrastructure at SMA Negeri 1 Purwakarta aims to determine the infrastructure so that the vision and mission of the school can be achieved, (2) the control of infrastructure at SMA Negeri 1 Purwakarta is carried out by inventory, storage, maintenance. (3) improving the quality of infrastructure at SMA Negeri 1 Purwakarta is carried out by preparing schedules, prioritized activities, time/schedule for use, assignments/appointments according to expertise.